Association of Learning Strategies and WorthGiving to Tasks in Academic Achievement of Isfahan Medical Students - Shekoofeh Sadat Rezazadeh; Bibi Eshrat Zamani; Bibi Eshrat Zamani; Yasamin Abedini; Hasan Babri (Kerman University of Medical Sciences, 2014)
Background & Objective: Given the importance of academic achievement in medical students and an effective role of motivational different variables in students academic achievement including worth giving to task and learning strategies this research investigated the association between learning strategies task value and academic achievement of medical students   Methods: This was a descriptive study and the sample size included all students in Isfahan University of Medical Sciences The statistical sample ie 251 of whom were selected by proportional sampling Method of data collection was using a standard questionnaire valid and reliable Data were analyzed using descriptive statistics independent sample ttest and regression   Results: Deployment replication strategies and mental rehearsal and organizational in students error level of error 005 was less than the average level But the uses of semantic expansion strategy and task value the students were more than the average weighted average (3) respectively On the one hand between the use of replication strategies and mental rehearsal and semantic expansion strategy task value there was a significant association with academic achievement in students   Conclusion: Teaching learning strategies preparing brochures and/or even deliver credit courses the use of learning strategies and study can be useful measures of students familiarity with the appropriate learning strategies On the other hand due to the effect levels task value on academic achievement attention should be given to the developing courses interests and educational needs of students to provide more attention